Digital Innovation of Election Administration Registration Application to Improve Accuracy of Legislative Candidate Data - Arief Fathur Rahman; Muhammad Yasin Simargolang; Novica Irawati (Bigint Computing Journal, 2025)
Currently, the data registration procedure required by the North Sumatra Provincial General Election Commission is still done traditionally. Therefore, all legislative candidates from political parties must directly provide the required data in document format or written sheets. As a solution to this problem, it is recommended that an application be used to check and register the data required by the North Sumatra Provincial General Election Commission. This application uses the PHP programming language, MySQL as a database, and the waterfall method will be applied to computerize the process, making it faster and more accurate. The design of this application consists of two elements: the North Sumatra Provincial General Election Commission administrator, who handles the checking and filtering of the required data for each legislative candidate, and the political party administrator, who inputs the data for the legislative candidate. The implementation of this application is expected to increase efficiency, reduce errors, and support transparency in the legislative candidate registration process.